Transaksi Bisnis Tembakau dalam Perspektif Hukum Ekonomi Syariah - Achmad Anas (Program Pascasarjana Universitas Ibrahimy, 2020)
Three basic economic activities are production, distribution, and consumption. Economic growth can be realized quickly, by maximizing one of the three. Economic growth that can create prosperity can be done in two ways: growth in production factors, both labor, and capital. Economic activities are concentrated in businesses in the form of production, partnerships, sales. The results of this study are there are several roles of the Indonesian Tobacco Farmers Association that were found, in the form of mediator, facilitator, advocacy. And there are also findings in the form of increased taxes and the distribution of tobacco excise revenue sharing funds that are not evenly distributed. There are also several findings, they are: the occurrence of economic activities in the form of partnerships carried out by tobacco farmers and entrepreneurs. The difference lies in the end that there is a transaction of buying and selling witnesses between tobacco farmers and entrepreneurs. So when partnering, the agreement must sell farmers' crops to partners, namely tobacco entrepreneurs. Of course, the transaction has met the provisions of Sharia Economic Law, when the conditions have been fulfilled, the transaction will be considered valid.